Future challenges in security and privacy for academia and industry 26th IFIP TC 11 International Information Security Conference, SEC 2011, Lucerne, Switzerland, June 7-9, 2011. Proceedings - Camenisch, Jan; Fischer-Hübner, Simone; Murayama, Yuko; Portmann, Armand; Rieder, Carlos (IFIP advances in information and communication technology, 2011)
This book constitutes the refereed proceedings of the IFIP WG 8.2 Working Conference "Researching the Future", Future IS 2011, held in Turku, Finland, in June 2011. The 17 revised full papers presented together with 4 panels and workshops were carefully reviewed and selected from numerous submissions. The papers are organized into 6 topical sections: how the future and the past are connected and inter-related; critical view of the future; technological futures; the future of information technology and work-related practices in health care; the future of industrial and institutional practices and outcomes through information technology; and the future of critical realism in IS research.